Moisture effects on the electrochemical reaction and resistance switching at Ag/molybdenum oxide interfaces - Yang, Chuan-Sen; Shang, Da-Shan; Chai, Yi-Sheng; Yan, Li-Qin; Shen, Bao-Gen; Sun, Young (Physical chemistry chemical physics : PCCP, 2016)
An important potential application of solid state electrochemical reactions is in redox-based resistive switching memory devices. Based on the fundamental switching mechanisms, the memory has been classified into two modes, electrochemical metallization memory (ECM) and valence change memory (VCM). In this work, we have investigated a solid state electrochemical cell with a simple Ag/MoO 3− x /fluorine-doped tin oxide (FTO) sandwich structure, which shows a normal ECM switching mode after an electroforming process. While in the lower voltage sweep range, the switching behavior changes to VCM-like mode with the opposite switching polarity to the ECM mode. By current-voltage measurements under different ambient atmospheres and X-ray photoemission spectroscopy analysis, electrochemical anodic passivation of the Ag electrode and valence change of molybdenum ions during resistance switching have been demonstrated. The crucial role of moisture adsorption in the switching mode transition has been clarified based on the Pourbaix diagram for the Ag-H 2 O system for the first time. These results provide a fundamental insight into the resistance switching mechanism model in solid state electrochemical cells. The crucial role of ambient moisture in the electrochemical processes and switching mode transition from electrochemical metallization memory (ECM) to valence change memory (VCM) is clarified based on the Pourbaix diagram for the Ag-H 2 O system and the Mo 5+ /Mo 6+ valence change.